Murder of a stacked librarian : a Scumble River mystery - Swanson, Denise (Swanson, Denise. Scumble River mysteries., 2013)
There's no place like Scumble River at Christmastime, and this year, school psychologist Skye Denison has twice as much to celebrate and to do. In addition to the usual holiday frenzy, Skye's wedding to police chief Wally Boyd is less than a week away, that is, if the groom isn't too busy working to attend. The town's sexy new librarian, Yvonne Osborn, has just been murdered, and the list of suspects is piling up faster than late fees on an overdue book. Yvonne's strict sense of right and wrong annoyed some townspeople and infuriated others. Did her high standards lead to her death? Skye is distracted by worries about what havoc the crazy Dooziers will wreak on her wedding day and whether she'll fit into her dress. But Skye can't afford to leave any page unturned because unless she works quickly to expose the scheming killer, her happy ending may be put on permanent hold.